PENGARUH FEAR OF MISSING OUT, GAYA HIDUP DAN KELOMPOK REFERENSI TERHADAP PERILAKU KONSUMTIF KULINER KEKINIAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PATTIMURA AMBON - Sampulawa, Hartiwi; Ayu Aisah Asnawi, Raden; Jeanete Saununu, Siska (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2025)
The culinary world is increasingly dynamic with the emergence of new trends that attract consumers, especially the younger generation. This phenomenon has not only changed the way people view and enjoy food, but has also created new consumption patterns, especially among the younger generation, including students. This study aims to determine the effect of Fear Of Missing Out (X1), Lifestyle (X2), and Reference Group (X3) on Consumptive Behavior (Y).The population used in this study were students of the Faculty of Economics and Business, Pattimura University Ambon, with a total sample studied of 140 samples. This research is located at the Faculty of Economics and Business, Pattimura University Ambon, the sampling method used is non probability sampling using purposive sampling technique. The data analysis method uses Partial Least Square (PLS) and the data is processed using the help of SmartPLS software version 3.3.3. The results showed that Fear Of Missing Out (fomo) has a positive and significant effect on consumptive behavior, Lifestyle has a positive and significant effect on consumptive behavior, Reference Group has a positive and singnifkan effect on consumptive behavior.